“We're on the ground, we know what needs to be done”: Exploring the role of Aboriginal Health Workers in primary health care - Jeyakumar, Ragavi; Patel, Bindu; Coombes, Julieann; Madden, Ty; Joshi, Rohina (Frontiers in Public Health, 2023)
Background Aboriginal Health Workers (AHWs) are core providers of primary health care (PHC) for First Nations peoples in Australia. However, the national AHW workforce is ageing and in short supply. There is a poor understanding of the factors contributing to this attrition from the perspectives of AHWs themselves. This study aimed to systematically explore the current functioning and sustainability of AHWs in NSW PHC by amplifying AHW voices. Materials and methods This study was co-designed with three Aboriginal health services in NSW. It included a literature review exploring the role of AHWs in NSW, and yarns with AHWs and their supervisors at participating services. The yarns were guided by the USAID-developed Community Health Worker Assessment and Improvement Matrix. Yarn transcripts were analysed using cyclical thematic analysis to identify key facilitators and challenges for AHW practice. Results The yarns highlighted five categories of change that are required to ensure AHW sustainability: community connection, recognition, value, support, and an inclusive health system. There are service-level actions in each of these categories which require a holistic, system-wide shift to support AHW retention. Conclusions The lived experiences of AHWs in NSW emphasise five key categories of change that are required to ensure workforce sustainability. It is evident that a system-wide paradigm shift to better include holistic approaches to health is necessary to truly ensure sustainability. Co-designing similar studies with ACCHOs across NSW can help inform this change.